2012
DOI: 10.4028/www.scientific.net/amm.178-181.2254
|View full text |Cite
|
Sign up to set email alerts
|

The Finished Product of Rubber Bearing Mechanical Performance Analysis in the Low Temperature

Abstract: In this paper, an experiment is carried out on compressive elastic modulus, shear modulus, silicon fat consistency and peel strength of synthetic rubber bearing and cold type natural rubber bearing produced in Shanghai Rubber Factory under low temperature condition. The experiment reveals the mechanical property of rubber bearing and change law of cooling temperature difference which offers reference and guidance for the selection of rubber bearing products under low temperature condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…e authors of [16][17][18] analyzed and studied the performance of rubber springs at low temperature; the results showed that low temperature has a significant effect on the properties of rubber. Österlöf et al [19][20][21] studied the relationship between the rubber model and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…e authors of [16][17][18] analyzed and studied the performance of rubber springs at low temperature; the results showed that low temperature has a significant effect on the properties of rubber. Österlöf et al [19][20][21] studied the relationship between the rubber model and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Select 45 kN as the conversion standard, and calculate λ N•45 when the prepressure is 57 kN, 65 kN, 75 kN, and 85 kN according to the theoretical formula (18); use formula (19) to calculate the dynamic parameters and compare with the test value, as shown in Figure 12. is method is named the theoretical DFCC prediction method (Method 1).…”
Section: Error Analysis Of the Dfcc Methodmentioning
confidence: 99%
“…In order to highlight the research focus and more clearly reveal the change rule of performance parameters with the prepressure, select a specific frequency and amplitude for comparison; only consider the relative change of performance parameters when the prepressure changes. According to the assumptions that the parameters of dynamic-static parameters increase in the same proportion with the change of prepressure, and according to formula (18), the following formula can be obtained:…”
Section: Dfcc and Parameter Calculationmentioning
confidence: 99%
See 1 more Smart Citation